[Health-related quality of life instruments and other patient-reported outcomes]. - Valderas, J; Ferrer, M; Alonso, J (2005)
In the last few years, many different instruments assessing health-related quality of life and the broader concept of Patient-Reported Outcomes (PRO) have been developed. Following the recommendations of the Scientific Advisory Committee of the Medical Outcomes Trust, the ePRO checklist provides a modular assessment for PRO instruments based on eight key attributes: conceptual and measurement model, reliability, validity, responsiveness, interpretability, respondent and administrative burden, alternative forms, and cross-cultural adaptation. Selected criteria describing each attribute in detail are also listed. The availability of explicit guidelines is expected to promote the development of better PRO measurement instruments.